Treatment strategy for treating atrial-esophageal fistula: esophageal stenting or surgical repair?. Issue 43 (October 2016) - Zhou, Bing; Cen, Xue-Jiang; Qian, Lin-Yan; Pang, Jie; Zou, Hai; Ding, Ya-Hui
Abstract: Introduction: Atrial-esophageal fistula (AEF) is a rare severe disease, which may be associated with radiofrequency catheter ablation (RFCA) of atrial fibrillation (AF) or intraoperative radiofrequency ablation of atrial fibrillation (IRAAF). Clinical Findings: We reported a case of a 67-year-old man with AEF following RFCA of AF, who treated with esophageal stenting and surgical repair. Outcomes: He was attacked by out-of-control sepsis and infectious shock after surgery and died. Literature review: We analyzed 57 relevant articles about AEF from 2003 to 2015 by searching PubMed database. According literatures, the most common symptoms were fever, rigor, sepsis, and neurologic symptoms. Chest computer tomography (CT) and contrast enhanced CT may be the reliable noninvasive diagnosis methods because of high sensitive for AEF. Conclusion: Make a definition diagnosis in time with early primary surgical repair may save their lives. Conservative treatment or esophageal stenting alone may not be a better choice for AEF patients.